Pre-flight expectations in the air transportation industry of South Africa: A confirmatory factor analytical approach - De Jager, Johan W.; Jan, Muhammad Tahir (National Academy of Management, 2016)
The purpose of this paper is to determine passenger’s expectations of personal activities offered at airports as part of airline transportation experience. Expectations of a sample of South African travellers were selected, they were enquired regarding their expectations of personal services rendered at an airport. Exploratory factor analysis was undertaken to extract the factors underlying the data. Two main factors were clearly extracted, namely, non-flight related paid services and auxiliary airport services, which were then confirmed through confirmatory factor analysis.